If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -10x = 21 + -17x Solving 6 + -10x = 21 + -17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17x' to each side of the equation. 6 + -10x + 17x = 21 + -17x + 17x Combine like terms: -10x + 17x = 7x 6 + 7x = 21 + -17x + 17x Combine like terms: -17x + 17x = 0 6 + 7x = 21 + 0 6 + 7x = 21 Add '-6' to each side of the equation. 6 + -6 + 7x = 21 + -6 Combine like terms: 6 + -6 = 0 0 + 7x = 21 + -6 7x = 21 + -6 Combine like terms: 21 + -6 = 15 7x = 15 Divide each side by '7'. x = 2.142857143 Simplifying x = 2.142857143
| -108-8x=8x+20 | | 6x+9=89-8x | | W-4w=2w+1-5w | | 120-4x=3x+15 | | 11-2x=5-5x | | -34-2x=6-10x | | 14-(2x+5)=-2x+9 | | 76-3x=7x+16 | | 5x+10=80-2x | | 8+12x=140+x | | 4(a-3)+2=3a-19 | | 2x-3=11x-93 | | 3x+24=10x-39 | | 11x-39=5x+3 | | 9-5x=6-6x | | 12x+9=6x+33 | | 10x-25=85 | | 8(x-3)+8=5x-22 | | 6(10x+3)+19x= | | 6(10x+3)+19= | | 0.36n=-0.29 | | -2.25=-1.25x | | .40x=-.10 | | 6+3x=4(x+2) | | (-28)+15y=17 | | 7n=63 | | -6+2c=3c-(6+5) | | -1.33=-1.33x | | -76-7x=7x+22 | | .66x=-1 | | 5=(-4)y-21 | | 5x+10=-68-8x |